Corrosion behaviour of nanocrystallines alloy 690 at high-temperature and high-pressure in simulated PWR secondary environment. (20th January 2021) - Li, Xiaoxian; Liu, Jiang; Liu, Junbiao; Zhu, Shengjian; Yan, Yangxian; Zhang, Xuehui; Liang, Tongxiang
Abstract: The influence of ultrasonic surface rolling treatment (USRT) on the corrosion behaviour of nanocrystallines (NC) alloy 690 at high temperature and high pressure in simulated PWR secondary environment was performed by using Raman spectrometer, X-ray photoelectron spectrometer (XPS) and scanning electron microscopy (SEM). After USRT, the average size and the thickness of NC surface layer could reach 55 nm and 1 μ m, respectively. Electrochemical measurements showed that the oxide film on the surface of NC alloy 690 was denser and more complete compared with coarse grained (CG) samples. The corrosion tests in ethanolamine (ETA) solution illustrated that the fine oxide particles were evenly distributed on the oxide film of NC alloy 690. The corrosion potential increased from −364 mV to −229 mV, while the corrosion current density dropped from 18.07 × 10 −8 mm 2 A cm −2 to 8.842 × 10 −8 mm 2 A cm −2 after USRT. By analysis, the inner layer of oxide film consisted of Cr2 O3, NiFe2 O4, and FeCr2 O4, while Ni hydroxides formed the major part of the outermost layer of film. A growth model of oxide films on alloy 690 at high-temperature and high-pressure in stimulated PWR secondary environments was proposed and discussed.